2000
DOI: 10.4049/jimmunol.164.1.398
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contribution of Fas- and Perforin-Mediated Mechanisms to the Cell-Mediated Cytotoxic Activity of Naive and In Vivo-Primed Intestinal Intraepithelial Lymphocytes

Abstract: Intestinal intraepithelial lymphocytes (IELs) are known to exert strong constitutive cytotoxic activity. In the present study we compared the Ag-specific cytotoxic activity and the effector mechanisms involved in non-Ag-primed, naive and in in vivo-primed IELs and splenic CD8 T cells. Ex vivo isolated naive CD8αα TCRαβ IELs, CD8αβ IELs, and splenocytes from lymphocytic choriomeningitis virus (LCMV)-specific TCR transgenic mice exert Ag-specific cytotoxic activity in a long-term, but not in a short-term, cytoto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 23 publications
(16 reference statements)
1
30
0
Order By: Relevance
“…Type a mucosal T cells have much in common with peripheral CD4 + or CD8ab + cells, but also show some gut-specific regulatory functions. Thus, CD8ab + TCRab IEL may exert some cytolytic functions [4], whereas resident (non-infiltrating) CD4 + TCRab cells often show a regulatory phenotype [3]. Type b TCRcd cells likely play a dual role in the regulation of protective immune responses and the regulation of epithelial layer integrity via the release of keratinocyte growth factor [1].…”
Section: Discussionmentioning
confidence: 99%
“…Type a mucosal T cells have much in common with peripheral CD4 + or CD8ab + cells, but also show some gut-specific regulatory functions. Thus, CD8ab + TCRab IEL may exert some cytolytic functions [4], whereas resident (non-infiltrating) CD4 + TCRab cells often show a regulatory phenotype [3]. Type b TCRcd cells likely play a dual role in the regulation of protective immune responses and the regulation of epithelial layer integrity via the release of keratinocyte growth factor [1].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the majority of CD8+ IELs express CD69, a marker of recently-activated lymphocytes [1]. Moreover, without in vitro activation, IELs are constitutively cytolytic [2][3][4][5], suggesting that they are not classical resting T cells. However, IELs have limited capacity for proliferation and they do not spontaneously produce cytokines [6,7], both of which are properties that belie the likelihood that they are fully-activated T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Immunostaining of Giardia-infected human intestinal tissues has demonstrated that these specimen's intraepithelial lymphocytes, which are mostly CD8 + T cells, are positive for T-cell restricted intracellular antigen (TIA)-1, but negative of Granzyme B, implying that these CD8 + T cells are resting cytotoxic cells (Oberhuber et al 1996). Furthermore, CD8 + IEL isolated from TCR transgenic mice exhibit antigen-specific perforin-and FasL-mediated cytotoxic activity toward intestinal epithelial cells and T cells (Corazza et al 2000, Melgar et al 2002. Potent FasLdependent cytolytic activity of CD8 + IEL toward enterocytes was also reported in graft-versus-host disease, which shares a number of the pathophysiological features of giardiasis (Corazza et al 2000).…”
mentioning
confidence: 99%
“…Furthermore, CD8 + IEL isolated from TCR transgenic mice exhibit antigen-specific perforin-and FasL-mediated cytotoxic activity toward intestinal epithelial cells and T cells (Corazza et al 2000, Melgar et al 2002. Potent FasLdependent cytolytic activity of CD8 + IEL toward enterocytes was also reported in graft-versus-host disease, which shares a number of the pathophysiological features of giardiasis (Corazza et al 2000). In graft versus host disease-associated intestinal inflammation, or upon intestinal bacterial infection, IEL express a high level of the integrin α Xβ 2 (Huleatt et al 1995).…”
mentioning
confidence: 99%